USING DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS' LISTENING ABILITY - Wini Rismayanti, - (2009)
The research applied to find out whether or not the dictogloss technique was effective to improve students' listening ability. The quasi-experimental research with the pre-test and post-test non-equivalent groups design used as the research method. The hypothesis was stated that the dictogloss technique was not effective to improve students' listening ability. The research involved 42 eleventh grade students of SMKN 14 Bandung. There were two groups involved in the research as the sample: experimental and control groups. The data was collected from listening test, questionnaire and interview. The listening test was conducted to know whether or not the dictogloss technique was effective. In addition, the questionnaire and interview were conducted in the experimental group only to know to what extend the dictogloss technique was effective in teaching listening. From the data obtained, the dictogloss technique was effective to improve students' listening ability since t obs for experimental was smaller than t crit (-6.188 < 2.086). It meant that t obs was outside the H0 area (H0 is rejected). Whereas, t obs for control group was between ± t crit (- 2.086 < - 0.338 < 2.086), which indicated that t obs was inside area. H0 is accepted. On the other hand, the data gained from questionnaire and interview showed that the dictogloss technique was also effective to improve other students' language competences, such as vocabulary, pronunciation and grammar. By using dictogloss technique, the listening materials were more meaningful, challenging, understandable, and interesting. However, students faced the obstacles when learning during the technique. For instances, they found difficulty to recognize the keywords because of the native speaker speed. Further, another difficulty was correcting the text due to students' weakness of grammar competence. Students had the solution to solve the obstacles such as working and sharing in group and asking their partner or teacher